Efficacy of feeding tiger puffer Takifugu rubripes on moon jellyfish with respect to nutritional composition and behavioural traits. (24th June 2017) - Miyajima‐Taga, Y.; Masuda, R.; Kurihara, A.; Komi, R.; Yamashita, Y.; Takeuchi, T.
Abstract: Although jellyfish blooms are serious nuisances for fisheries and other industries, the utilization and nutritional value of by‐catch jellyfish has drawn public attention. Here, we evaluated the efficacy of feeding tiger puffer Takifugu rubripes with moon jellyfish Aurelia sp. using 20‐day rearing experiments. Feeding on jellyfish had no positive effect on growth performance, although it significantly reduced neutral lipids and increased proportions of polar lipids, n −3 and n −6 highly unsaturated fatty acids (HUFAs), especially arachidonic and docosahexaenoic acids, and taurine. Supplemental feeding on jellyfish plus pellets elevated activity and responsiveness in the fish, with no effect on burst swimming speed or prevention of aggressive biting by siblings. The present research suggests that feeding on jellyfish improves body composition and some behaviours in tiger puffers. As cultured fish tend to accumulate excessive amounts of lipids from lipid‐rich pellets that can induce an unhealthy condition, and behavioural deficits of hatchery‐reared fish reduce survival after release in the wild, we propose the use of jellyfish as a supplemental diet in the nursery production of tiger puffer. Moreover, feeding on jellyfish can overcome deficiencies in alternative soy‐material feeds by supplying phospholipid, HUFAs, or taurine.